Pemberdayaan Masyarakat Melalui Hilirisasi Umbi Ganyong Menjadi Anyong Cookies di Desa Bumi Pajo - Nursani; Khas Sukma Mulya; Muhammad Akbar; Rizky Ameliya; Muhammad Rizkan; Fajrin Hardinandar; Syafruddin (SEWAGATI: Jurnal Pengabdian kepada Masyarakat, 2026)
Bumi Pajo Village, Donggo Sub-district, Bima Regency, is the main producing area of canna (Canna edulis), locally known as kalo dana, yet most of the harvest is still sold as fresh tubers at low prices due to limited processing knowledge and business management skills. This community service program aimed to downstream canna tubers into a value-added food product, "Anyong Cookies," through the Integrated Local Agroindustry Empowerment Model (ILAEM). The program used a Participatory Action Research (PAR) approach comprising five stages: potential identification, product downstreaming, capacity building, business and digital marketing management, and sustainability development. Activities included flour-making training, cookies production, business feasibility analysis (HPP and BEP), brand and packaging development, and digital marketing assistance. Results showed substantial increases in participants' knowledge and skills, from an average of 8-32% before the program to 86-100% afterward, along with the establishment of a marketable product with its own brand and packaging. These findings indicate that integrating product innovation with entrepreneurship capacity building produces a more sustainable model for local food downstreaming and rural economic empowerment.